2014
DOI: 10.1111/een.12156
|View full text |Cite
|
Sign up to set email alerts
|

Larval food composition affects courtship song and sperm expenditure in a lekking moth

Abstract: 1. Variation in larval food composition can have far-reaching effects on the adult phenotype of insects. To maximise reproductive output, it is therefore beneficial if insects are able to plastically adapt to nutritional cues in their larval diet.2. The expression of sexual traits implicated in pre-and postcopulatory sexual selection of the lesser wax moth, Achroia grisella Fabricius, across different rearing environments of varying diet composition was investigated.3. Moths reared on diet with relatively low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…However, the fact that PC1 and PC3 in our study both peak at a specific P:C ratio demonstrates that it matters what nutrients these calories are coming from. The small angle ( θ = 9.74°) between the linear nutritional vectors, the lack of difference in the nutritional gradients from our sequential model and the similar optimal P:C ratio for PC1 and PC3 (1 : 1.5 and 1 : 1, respectively) indicate that both vectors of CHC expression are maximized at an almost equal intake of P and C. Our work therefore adds to the growing list of studies showing that the balanced intake of specific nutrients are key to the condition‐dependent expression of male sexual traits (Maklakov et al ., ; South et al ., ; Fedina et al ., ; Sentinella et al ., ; Harrison et al ., ; Cordes et al ., ; House et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that PC1 and PC3 in our study both peak at a specific P:C ratio demonstrates that it matters what nutrients these calories are coming from. The small angle ( θ = 9.74°) between the linear nutritional vectors, the lack of difference in the nutritional gradients from our sequential model and the similar optimal P:C ratio for PC1 and PC3 (1 : 1.5 and 1 : 1, respectively) indicate that both vectors of CHC expression are maximized at an almost equal intake of P and C. Our work therefore adds to the growing list of studies showing that the balanced intake of specific nutrients are key to the condition‐dependent expression of male sexual traits (Maklakov et al ., ; South et al ., ; Fedina et al ., ; Sentinella et al ., ; Harrison et al ., ; Cordes et al ., ; House et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…[54]). There are, however, far fewer studies that explore the effects of a poor juvenile diet on sperm reserves and sperm replenishment rates (but see: [35, 40]). We found that both sperm reserves and replenishment rates were affected by a male’s early diet in an age-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[38, 39]). This could shift the relative allocation of resources to sperm competitiveness versus attractive ornaments [40]. For example, greater investment in larger body size or weaponry can result in smaller testes and ejaculates [41, 42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the expected negative relation between testes mass and weaponry was convincingly demonstrated in the beetle Onthophagus nigriventris (Simmons & Emlen, ), in the myobatrachid frog Crinia georgiana (Parker et al ., ), and across pinniped species (Fitzpatrick et al ., ), and male bustards Chlamydotis undulata that invest most heavily on extravagant sexual displays to attract mates have accelerated senescence in ejaculate quality and fertility (Preston et al ., ). However, no relationship between RTS and horn size was found across species in the genus Onthophagus , possibly because of evolutionary changes in the developmental mechanisms regulating trait growth (Simmons & Emlen, ), or between the size of horns/antlers and RTS across species within the ungulate order Artiodactyla , (Ferrandiz‐Rovira et al ., ), and no evidence for a trade‐off between pre‐ and post‐copulatory traits was found in male Mongolian gerbils Meriones unguiculatus (Shen et al ., ) or the lesser wax moth Achroia grisella (Cordes et al ., ), a lekking species.…”
Section: Trade‐offsmentioning
confidence: 99%